New insights concerning homology of the oral region and ambulacral system plating of pentaradial echinoderms. (10th May 2017) - Sumrall, Colin D.
Abstract: Universal elemental homology (UEH) underpins recent understanding of peristomial and ambulacral elemental homology of pentaradiate echinoderms by providing a uniform set of terminology to construct phylogenetic characters. Variation in the expression of these elements provides evidence for phylogenetic relationships. Two nonhomologous sets of plates border the peristome and are associated with two nonhomologous sets of floor plates forming the ambulacral food groove. Some edrioasteroid-grade and eocrinoid-grade echinoderms have ambulacral systems formed from oral frame plates and adradial floor plates, whereas most blastozoans and crinoids bear oral plates and abradial floor plates. These plates are expressed in a variety of ways among echinoderms, but nearly all can be reconciled with the underlying model. Arguments against UEH are methodologically flawed and confuse many terms and interpretations.